An Accidental death benefits table using Whittaker-Henderson graduation - Palma, Charmaine L.
This paper intends to conduct a review of a particular life insurance company's current mortality experience due to accidental death and if deemed appropriate, develop a mortality table that may be used for valuation and/or pricing of accidental death benefits specific to that company. The basic material for the study will be derived from standard and medically underwritten accidental death benefit riders attached to ordinary life policies issued from years 1993 to 2003. Being the most recent data available, the years between 2000 and 2003 policy anniversaries are selected to comprise the period of observation. The seriatim method for calculating exposures will be employed, tabulating deaths on an age-last-birthday basis. Obtaining graduated rates will be done using Whittaker-Henderson's technique, after which extrapolation of the rates to the extreme ages will be undertaken to close the life table. Adequacy tests will also be performed to measure whether the graduated values' degree of fit and smoothness are within acceptable limits.
Computer print out.
Keywords: Survivors' benefits; Mortality -- Statistics .